A invisibilidade da prática do contrabando transnacional de migrantes: intercorrências nas políticas do Brasil e da Argentina no período de 2010-2018 - Pinto, Joseane Mariéle Schuck (Universidade do Vale do Rio dos Sinos, 2022)
The research aims to investigate the production of public policies of international cooperation adopted between Brazil and Argentina, driven by the Agreements and Conventions assumed by them. From this, we intend to know and understand their constitution in relation to the confrontation and prevention of transnational smuggling of migrants between 2010 and 2018. Thus, this study starts from the following question: what is the political-legal apparatus of cooperation between Brazil and Argentina for the confrontation and prevention of transnational smuggling of migrants at their borders? And how is such apparatus, as public policy, being operated at the borders between the two countries? Similarly, it seeks to determine how cooperation is being implemented in terms of actions, awareness campaigns, efforts, mechanisms, and joint public policies aimed at preventing the practice of migrant smuggling/trafficking, with special attention to protecting the human rights of the migrant community - the subjects of rights. Besides the highlighted points, the operation of repression/combat measures and securitization of border control policies are examined. Thus, after the analytical construction of the research topic, it was found that the political actions taken to address the complex scenario of migrant smuggling have been viewed from two angles: the first, aimed at tackling the crime itself and its repression, which is perfected by the securitization agenda adopted by Brazil; and the second, aimed at actions to protect and protect the human rights of migrants, with a social policy bias, which would help minimize the invisibility of this reality. It remains evident that in the period from 2010 to 2018, with reflection in the present day, the category of migrant smuggling and its occurrence did not consist in a concern for the Brazilian state, in the sense of debating and elaborating state political actions for its prevention, with a view to the protection of migrants. What can be observed is the intention to include it in the debate of the IV National Plan, which will be implemented in 2023. In the Argentinean context, the smuggling/trafficking of migrants has been taken into consideration, that is, it´s understood as a State policy aimed at prevention, and it is notorious for its focus on human rights and their protection. Regarding the procedure adopted in this research, it is characterized in a qualitative approach, with documentary and bibliographic analysis, on a national and international level, as well as the consultation of domestic legislation in Brazil and Argentina, regarding existing public policies on the subject of study. A survey was carried out of the conventions, protocols, and other international instruments that served to help understand the reality studied. The second part of the data collection (primary) includes semi-structured interviews with key players directly involved with the studied theme. The construction of the methodological field, from the operational analytical categories, counted on the theoretical referential of Stephen Castles (migration governance, security, securitization); Alexander Betts (undocumented); Lindomar Boneti (public policies); Zygmunt Bauman (globalization, human discard, exclusion); Seyla Benhabib and Donatella Di Cesare (citizenship, exclusion and invisibility processes); Giorgio Agamben (state of exception, bare life, biopolitics); Ratna Kapur (transnational migration), Delmos Jones (transmigrants).

La investigación tiene como objetivo investigar la producción de políticas públicas de cooperación internacional adoptadas entre Brasil y Argentina, impulsadas por los Acuerdos y Convenios asumidos por ellos. A partir de ello, se pretende conocer y comprender su constitución en relación al enfrentamiento y prevención del tráfico transnacional de migrantes entre 2010 y 2018. Así, este estudio parte de la siguiente pregunta: ¿cuál es el aparato político-jurídico de cooperación entre Brasil y Argentina para el enfrentamiento y la prevención del tráfico transnacional de migrantes en sus fronteras? ¿Y cómo se opera dicho aparato, como política pública, en las fronteras entre ambos países? Del mismo modo, se busca determinar cómo se está implementando la cooperación en términos de acciones, campañas de sensibilización, esfuerzos, mecanismos y políticas públicas conjuntas destinadas a prevenir la práctica del tráfico/trata de migrantes, con especial atención a la protección de los derechos humanos de la comunidad migrante – los sujetos de derechos. Además de los puntos destacados, se examina el funcionamiento de las medidas de represión/combatientes y la securitización de las políticas de control de fronteras. Así, después de la construcción analítica del tema de investigación, se constató que las acciones políticas tomadas para enfrentar el complejo escenario del tráfico de migrantes han sido vistas desde dos ángulos: el primero, dirigido al enfrentamiento del propio delito y su represión, que se perfecciona con la agenda de securitización adoptada por Brasil; y el segundo, dirigido a las acciones de protección y resguardo de los derechos humanos de los migrantes, con un sesgo de política social, que ayudaría a minimizar la invisibilidad de esta realidad. Queda evidente que en el período de 2010 a 2018, con reflejo en la actualidad, la categoría de tráfico de migrantes y su ocurrencia no consistió en una preocupación para el Estado brasileño, en el sentido de debatir y elaborar acciones políticas estatales para su prevención, con miras a la protección de los migrantes. Lo que se observa es la intención de incluirlo en el debate del IV Plan Nacional, que se implementará en 2023. En el contexto argentino, el tráfico/trata de migrantes ha sido tomado en consideración, es decir, se entiende como una política de Estado orientada a la prevención, y es notorio su enfoque en los derechos humanos y su protección. En cuanto al procedimiento adoptado en esta investigación, se caracteriza en un enfoque cualitativo, con análisis documental y bibliográfico, a nivel nacional e internacional, así como la consulta de la legislación interna de Brasil y Argentina, en cuanto a las políticas públicas existentes sobre el tema de estudio. Se realizó un relevamiento de las convenciones, protocolos y otros instrumentos internacionales que sirvieron para comprender la realidad estudiada. La segunda parte de la recolección de datos (primaria) incluye entrevistas semiestructuradas con actores clave directamente involucrados con el tema estudiado. La construcción del campo metodológico, a partir de las categorías analíticas operativas, contó con los referentes teóricos de Stephen Castles (gobernanza migratoria, seguridad, securitización); Alexander Betts (indocumentados); Lindomar Boneti (políticas públicas); Zygmunt Bauman (globalización, descarte humano, exclusión); Seyla Benhabib y Donatella Di Cesare (ciudadanía, procesos de exclusión e invisibilidad); Giorgio Agamben (estado de excepción, vida desnuda, biopolítica); Ratna Kapur (migración transnacional), Delmos Jones (transmigrantes).
Keywords: Argentina; Brasil; Contrabando de migrantes; Cooperação; Governança migratória; Migração transnacional; Políticas públicas; Securitização; Transmigrantes; Migrant smuggling; Cooperation; Migratory governance; Transnational migration; Public policy; Securitization; Transmigrants; Tráfico de migrantes; Cooperación; Gobernanza migratoria; Migración transnacional; Securitización; ACCNPQ::Ciências Humanas::Sociologia